Effect of a Structured Physical Exercise Program on Cardiorespiratory Function in Patients with Chronic Obstructive Pulmonary Disease - Aminah, Aminah; Astania, Sella Erin; Noermalita, Azahra Mona (Institute of Accounting Research and Novation (IARN), 2024)
Chronic Obstructive Pulmonary Disease (COPD) is a progressive respiratory condition characterized by airflow limitation and significant morbidity, impacting the quality of life of affected individuals. This research investigates the effects of a structured physical exercise program on cardiorespiratory function in patients with COPD. A total of 100 participants with a confirmed diagnosis of COPD were enrolled in a 12-week exercise intervention, which included aerobic and strength training activities tailored to individual capabilities. Outcomes were assessed using the six-minute walk test (6MWT), spirometry, and quality of life measurements via the St. George’s Respiratory Questionnaire (SGRQ). Results demonstrated significant improvements in exercise capacity, with participants increasing their 6MWT distances by an average of 30 meters (p < 0.01). Additionally, there was a notable reduction in dyspnea, as measured by the Modified Medical Research Council (mMRC) scale, and an overall enhancement in quality of life scores. These findings suggest that a structured exercise program can effectively improve cardiorespiratory function and quality of life in patients with COPD. Future studies are recommended to explore long-term effects and adherence strategies to further enhance the benefits of exercise in COPD management.